Family factors associated with pregnancy in adolescents in a child maternal center of Lima - Perú, 2014 - Arnao-Degollar, Verónica Antoinette (2020)
Objective: To determine what are the family factors that are associated with pregnancy in adolescents treated in the Maternal and Child Center "José Gálvez" during 2014. Material and methods: Study of cases and controls, with a sample formed by 60 teenage primigests (cases) and 60 adult primigests (controls). It was applied a questionnaire of 15 items, including 11 family factors. The data were emptied into a matrix of the SPSS version 24 program and the chi-square and the Odd-Ratio were used as a statistical test with a 95% confidence interval. Results: Family factors that presented a significant association with teenage pregnancy were having an incomplete family (OR: 2,625; 95% CI: 1,211-5,691), living in the absence of one of the parents (OR: 2,891; 95% CI : 1,356-6,161), existence of family violence (OR: 2,529; 95% CI: 1,188-5,387), suffering from physical violence (OR: 3,800; 95% CI: 1,001-14,584), poor communication with the father ( OR: 2,307; 95% CI: 1,097-4,850), poor communication with the mother (OR: 3,059; 95% CI: 1,357-6,896), and not consulting the mother about sexuality (OR: 2,366; 95% CI : 1,111-5,040). Conclusions: There are several family factors that favor the presence of teenage pregnancy, especially those related to family violence, living with parents, the existence of appropriate communication with the father and / or mother, and the fact that they can consult the mother about sexuality issues.